Pengembangan Model Pembelajaran Pendidikan Agama Islam Yang Mendorong Moderasi Beragama Pada Peserta Didik - Fauziyah Nurhayati; Muhamad Rifa’i Subhi (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
Islamic Religious Education (PAI) has a very significant role in shaping students' character and views towards diversity and religion. In the context of an increasingly complex and multicultural society, it is important to develop a PAI learning model that encourages religious moderation in students. This research aims to identify, design and test a PAI learning model that can effectively facilitate a moderate and tolerant understanding of religion in students.